Comprehensive evaluation of physiological response and cold tolerance of domesticated Cinnamomum camphora (L.) Presl under low temperature stress - Ding,Jinping; Zhang,Zongying; Zhu,Xinyu; Hou,Ying (PeerJ, 2024)
Improving cold tolerance is one of the key techniques for introducing southern tree species to northern China. To provide a theoretical basis for the introduction and cold-tolerance cultivation of Cinnamomum camphora (L.) Presl, the physiological response and cold tolerance of acclimated Cinnamomum camphora (L.) Presl trees were studied. In this experiment, the cold tolerance physiological indexes of Cinnamomum camphora (L.) Presl were measured in an indoor artificial simulation of low temperature stress. The results showed that under low temperature stress, the Cinnamomum camphora (L.) Presl are cultivated for 1 year, 5 years, 10 years and 15 years, respectively, at 4 °C, 0 °C, −5 °C, −10 °C, −15 °C and −20 °C. The relative electrical conductivity change ranges were 26.26%–13.98%, 30.71%–19.24%, 37.36%–27.18%, 44.16%–32.24%, 63.21%–52.05%, and 86.43%–76.24%; the MDA content ranges were 12.10 mmol/g–3.25 mmol/g, 15.90 mmol/g–4.08 mmol/g, 10.53 mmol/g–2.05 mmol/g, 23.20 mmol/g–5.35 mmol/g, 31.30 mmol/g–5.89 mmol/g, and 36.47 mmol/g–8.13 mmol/g, respectively. The relative water content change ranges were 95.35%–65.92%, 71.36%–49.67%, 54.67%–34.89%, 43.12%–23.12%, 26.03%–11.21%, and 23.03%–8.15%, respectively. At the same stress temperature, these indices decreased with increasing cultivation time, and the degree of membrane damage was reduced accordingly. The osmoprotectants were soluble protein, soluble sugar, and free proline which were increased gradually with cultivation time. at 4 °C, 0 °C, −5 °C, −10 °C, −15 °C and −20 °C, the soluble protein content change ranges were 3.51–6.18 mg/g, 6.24–9.95 mg/g, 9.44–19.59 mg/g, 14.23–28.36 mg/g, 17.34–33.19 mg/g, and 25.15–32.23 mg/g. the soluble sugar content change ranges were 9.64-26.97 mg/g, 15.37–39.86 mg/g, 26.63–53.97 mg/g, 45.49–76.75 mg/g, 52.74–81.24 mg/g, and 55.61–85.34 mg/g. the free proline content change ranges were 55.83–85.23 µg/g, 68.95-89.87 µg/g, 95.38-214.38 µg/g, 219.19-389.89 µg/g, 321.28-453.65 µg/g, and 381.23-478.96 µg/g, respectively. The osmoprotectants increased the cell stability and enhanced the cold tolerance of Cinnamomum camphora (L.) Presl. Protective enzyme activity were catalase, superoxide dismutase, peroxidase which were increased gradually with cultivation time, catalase reached a maximum at about −15 °C SOD reached a maximum at about −5 °C and POD reached a maximum at about −10 °C. These results indicated that the leaves of Cinnamomum camphora (L.) Presl could reduce stress damage by increasing the activity of antioxidant enzymes to clear the active oxygen in the body. A principal component analysis showed that the relative water content, soluble protein content, soluble sugar content, and superoxide dismutase activity could be used as important indexes for cold hardiness in Cinnamomum camphora (L.) Presl. The comprehensive evaluation showed that with the increase of domestication cultivation years, Cinnamomum camphora (L.) Presl. cold tolerance gradually improved.
Keywords: Cinnamomum camphora (L.) Presl; Cold tolerance; Domestication cultivation; Low temperature stress; Physiological index